IMPLEMENTASI SISTEM APLIKASI AKUNTANSI PADA UMKM SIKOP ARRUM BATIK TULIS LAMPUNG - PULUNG WICAKSONO DWI ANGGORO; Yafet Nuh Karamoy; Surya Prasetya Trihatmaja; Jessica Gita Elvira Thanos; Salim Salim Salim (Universitas Malahayati, 2025)
This study analyzes the impact of implementing a computerized accounting information system on enhancing operational efficiency and the accuracy of financial reporting in micro, small, and medium enterprises (SMEs). Using a descriptive qualitative approach, the research conducts a comparative analysis of financial recording conditions before and after the implementation of Accurate Accounting Version 5 application on a traditional batik textile enterprise in Lampung. Data collection involved direct observation, in-depth interviews with business owner, and documentation of financial reports from 2022-2024. The findings reveal that prior to implementation, the SME relied on manual recording systems that produced unstructured financial statements not in compliance with the Indonesian Accounting Standard for Micro, Small, and Medium Entities (SAK EMKM). Following the implementation of the cloud-based application, transaction recording became automated, financial statements (balance sheet and income statement) were generated in real-time, and the accuracy of cash management improved significantly. Recording errors were drastically reduced compared to the manual system, and the business owner achieved continuous monitoring of cash flow and financial performance. This research contributes to empirical understanding of the benefits of adopting accounting information system technology for traditional SMEs and provides practical evidence of improvements in operational efficiency, reporting transparency, and support for more informed business decision-making. The research findings can serve as a reference for policymakers and SME practitioners in adopting computerized accounting systems to enhance competitiveness and business sustainability.